Hubungan Derajat Klasifikasi Gagal Jantung Kongestif Terhadap Kepatuhan Terapi Medis Dan Tingkat Kepuasan Pasien Di Rumah Sakit Fatmawati Jakarta Selatan - Ulfah N Karim; Aliana Dewi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Heart failure classified in four stages which includes first stage, second stage, third stage, and fourth stage. Congestive heart failure patients are often re-hospitalized in hospital because of the reccurence. This research purposed to know the correlation between classifaction congestive heart failure to medical therapy compliance and patient satisfaction level in Fatmawati Hospital South Jakarta. This research used correlative descriptive design with quantitative research and cross sectional approach. The sampling technique in this research used a total sampling with 38 patients. Based on the research results that prove with p value = 0,000 < 0,05 which mean there’s significant correlation between classification stages of congestive heart failure to medical therapy compliance, with the value of r = 0,796 which show that there’s an intense correlation. This is proven with p value = 0,000 < 0,05 which mean there’s significant correlation between classification stages of congestive heart failure to medical therapy compliance, with the value of r = 0,796 which show that there’s an intense correlation. This is proven with p value = 0,000 < 0,05 which mean there’s significant correlation between classifaction stages of congestive heart failure to patient satisfaction level with the value of r = 0,606 which show that there’s an intense correlation. Rom the research result is expected that the patients can improve their medical therapy compliance to avoid the risk of reccurence for the re-hospitalized patients.